The Effect Of The Production Quality Of The Artificial Intelligence-Based Television Film Legenda Bertuah On Audience Satisfaction - Devina Rizkya Almira (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Devina Rizkya Almira 44221309, The Effect of Artificial Intelligence Based Legend of Luck Television Film Production Quality on Audience Viewing Satisfaction This study aims to determine the effect of the quality of the Legend of Adventure television program on Trans7 based on Artificial Intelligence AI on audience viewing satisfaction. The development of Artificial Intelligence AI technology has brought changes in the production process of television programs, including in the visual, audio, content presentation, and effectiveness of information delivery. Therefore, this study examines the extent to which the quality of the production of the resulting programs can affect the level of audience viewing satisfaction. This study uses a quantitative approach with a survey method. The population in this study was the audience who had watched the Legend of the Lucky program on Trans7, with a sample determined using a purposive sampling technique of 130 respondents. The data collection technique was carried out through the distribution of questionnaires using the Likert scale. Data analysis used validity test, reliability test, descriptive analysis, normality test, linearity test, simple linear regression test, determination coefficient test, and partial test (t test) with the help of IBM SPSS Statistics version 25. The results of the study show that the quality of the Legend of Luck television program based on Artificial Intelligence AI has a significant effect on audience viewing satisfaction. The results of the hypothesis test showed that H was accepted and H was rejected, which means that there was an influence between the quality of television programs based on Television Production Theory as an independent variable on audience viewing satisfaction based on Expectation Confirmation Theory as a dependent variable. The better the quality of the program production shown, the higher the level of satisfaction felt by the audience.